Applied computer science for GGOS observatories : communication, coordination and automation of future geodetic infrastructures - Neidhardt, Alexander (Springer, 2017)
This book combines elementary theory from computer science with real-world challenges in global geodetic observation, based on examples from the Geodetic Observatory Wettzell, Germany. It starts with a step-by-step introduction to developing stable and safe scientific software to run successful software projects. The use of software toolboxes is another essential aspect that leads to the application of generative programming. An example is a generative network middleware that simplifies communication. One of the book's main focuses is on explaining a potential strategy involving autonomous production cells for space geodetic techniques. The complete software design of a satellite laser ranging system is taken as an example. Such automated systems are then combined for global interaction using secure communication tunnels for remote access. The network of radio telescopes is used as a reference. Combined observatories form coordinated multi-agent systems and offer solutions for operational aspects of the Global Geodetic Observing System (GGOS) with regard to "Industry 4.0."- Resumé vydavatel
Keywords: geodezie; softwarové inženýrství; astronomická geodezie; geodesy; software engineering; astronomical geodesy; elektronické knihy; monografie; electronic books; monographs